2010
DOI: 10.1002/j.1556-6978.2010.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Climate, Stress, and Research Integrity Among Research Counselor Educators: A Preliminary Study

Abstract: In this quantitative study, 187 counselor educators at research institutions reported engaging in responsible conduct of research (RCR), with a few individuals reporting deviations from ethical behavior. Tenure-seeking faculty members indicated a greater likelihood of deviating from acceptable research practices than did tenured faculty members. The psychological meaningfulness of one's department and research ethics training positively related to engagement in RCR, explaining 18% of the variance. Implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Netting and Nichols-Casebolt (1997) conducted focus groups of social work faculty members and doctoral students and found that faculty and students were unclear about how to determine authorship credit and that doctoral students reported receiving little guidance from faculty on how to negotiate such decisions. In a study of self-reported research conduct among counselor educators, Wester, Willse, and Davis (2010) found that 15% of faculty reported being very or extremely unlikely to have authorship conversations with students and colleagues before beginning a project and that more than 15% of faculty members would be somewhat, very, or extremely likely to insist on being the first author on a student's thesis, dissertation, or other student research project. From these studies of counselor education, psychology, and social work, it seems that authorship practices are at times unclear, unstated, or disputed.…”
Section: Authorship Decisions In Practicementioning
confidence: 99%
“…Netting and Nichols-Casebolt (1997) conducted focus groups of social work faculty members and doctoral students and found that faculty and students were unclear about how to determine authorship credit and that doctoral students reported receiving little guidance from faculty on how to negotiate such decisions. In a study of self-reported research conduct among counselor educators, Wester, Willse, and Davis (2010) found that 15% of faculty reported being very or extremely unlikely to have authorship conversations with students and colleagues before beginning a project and that more than 15% of faculty members would be somewhat, very, or extremely likely to insist on being the first author on a student's thesis, dissertation, or other student research project. From these studies of counselor education, psychology, and social work, it seems that authorship practices are at times unclear, unstated, or disputed.…”
Section: Authorship Decisions In Practicementioning
confidence: 99%
“…The ACA Code of Ethics (ACA, 2005) states, "Counselors do not engage in misleading or fraudulent research, distort data, misrepresent data, or deliberately bias their results" (Standard, G.4.a.). In a study of 187 counselor educators and doctoral students, Wester et al (2010) found 3% reporting the likelihood that they would falsify data to receive a grant and 3% would falsify data to get published. Falsification of data has serious implications for clinical practice and is contrary to publishing ethical research.…”
Section: Discussionmentioning
confidence: 99%
“…When working with minors, researchers should seek and receive consent from legal guardians before ever talking to minors or asking them to assent to participate in one's study. Wester, Willse, and Davis (2010) found 7% of counseling professionals (13 out of 187 participants) reported that they were unlikely to gain consent from a legal guardian before collecting data from an individual under the age of 18. Mann (2008) suggested researchers should include an oral presentation in addition to the written consent form to ensure all participants have a solid understanding of the procedures, risks, and benefits of any study.…”
Section: Informed Consentmentioning
confidence: 99%
See 2 more Smart Citations